2008
DOI: 10.1080/09540260802397537
|View full text |Cite
|
Sign up to set email alerts
|

Asian models of excellence in psychiatric care and rehabilitation

Abstract: In Asia, like other regions, the circumstances for psychiatric care and rehabilitation impose various limitations on us. However, committed professionals have been creating innovative models of excellence, which are culturally appropriate and clinically effective. In this paper, seven innovative models of psychiatric care and rehabilitation are presented. The Nitte project in India provides a comprehensive free rural psychiatric service, while transforming the 'brain drain' problem to 'brain circulation' coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…The Uterature from such middle-income settings, for example many of the countries of Eastern Europe and South America (Knapp et al 2007;Semrau et al 2011;Razzouk et al, in press), indicates that modest levels of resource are usually aUocated for mental health care compared with commurücable and infectious diseases (Razali, 2004;Al-Krenawi, 2005;Furedi et al 2006;Akiyama et al 2008;Janse van Rensburg, 2009;Sharifi, 2009;Rodriguez, 2010). In addition, as resources aUow, the BCM indicates that the five elements of Limited speciaiist staff provision of: 9 training and supervision 9 Talking and psycho-social of primary care staff treatments 9 Pharmacological treatments 9 consultation-liaison for complex cases 9 out-patient and in-patfent assessment 9 treatment for cases which cannot be managed in primary care Out-patient/ambulatory dinics 9 Community mental health teams 9 Talking and psycho-social 9 Acute tn-patient care treatments 9 Pharmacological treatments 9 Long-term community-based residential care 9 Work and occupation > 3.…”
Section: Medium-income Settingsmentioning
confidence: 95%
“…The Uterature from such middle-income settings, for example many of the countries of Eastern Europe and South America (Knapp et al 2007;Semrau et al 2011;Razzouk et al, in press), indicates that modest levels of resource are usually aUocated for mental health care compared with commurücable and infectious diseases (Razali, 2004;Al-Krenawi, 2005;Furedi et al 2006;Akiyama et al 2008;Janse van Rensburg, 2009;Sharifi, 2009;Rodriguez, 2010). In addition, as resources aUow, the BCM indicates that the five elements of Limited speciaiist staff provision of: 9 training and supervision 9 Talking and psycho-social of primary care staff treatments 9 Pharmacological treatments 9 consultation-liaison for complex cases 9 out-patient and in-patfent assessment 9 treatment for cases which cannot be managed in primary care Out-patient/ambulatory dinics 9 Community mental health teams 9 Talking and psycho-social 9 Acute tn-patient care treatments 9 Pharmacological treatments 9 Long-term community-based residential care 9 Work and occupation > 3.…”
Section: Medium-income Settingsmentioning
confidence: 95%
“…Most beds are used for the treatment of long-term patients. Reform in Japan has been occurring gradually since the 1990s as a result of the emphasis now being placed on community mental health care services, and the creation of alternatives to long-stay wards, including community group homes [43,47]. Chan et al (2007) reported on the transition of former long-stay patients to a purpose-built supported group residence in Kochi, Japan, with a capacity to house up to 20 residents [47].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 99%
“…In the absence of a welfare network and limited public funding for vocational rehabilitation services, there may be greater scope for entrepreneurial initiatives such as social enterprises [43,44]. The Yu-Li psychiatric rehabilitation model reports positive outcomes for former long-stay patients living in community residential services in a township in Taiwan [45].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…There is great heterogeneity within the Asia‐Pacific (A‐P) region, with an array of sociodemographic influences that impact on psychiatric care (Lo et al, ). Previous reviews of rehabilitation practice in Asia have demonstrated examples of innovative models of excellence that have been created to maximize the natural attributes of nations within the region, with the intent of providing benefit to people suffering from severe mental illness (SMI) with minimal expense (Akiyama et al, ; Chandrashekar, Prashanth, Kasthuri, & Madhusudhan, ).…”
Section: Introductionmentioning
confidence: 99%